PERAN PROGRAM TAHFIZ DALAM MENGUATKAN SPIRITUALITAS DAN MOTIVASI BELAJAR PESERTA DIDIK MADRASAH IBTIDAIYAH TAHFIZUL QUR’AN JAMILURRAHMAN YOGYAKARTA - Nurwahidah, Yelis; Ali, Waode Rabiah Nazwa; Syifa, Nur Asy; Aisyah, Aisyah; Ningsih, Sri (STKIP Pesisir Selatan, 2025)
This study aims to analyze the role of the tahfiz program in strengthening students’ spirituality and learning motivation at Madrasah Ibtidaiyah Tahfizul Qur’an Jamilurrahman Yogyakarta. The main focus is to understand how the tahfiz activity not only develops students’ Qur’anic memorization skills but also contributes to the cultivation of moral values, discipline, and enthusiasm for learning. This research employs a descriptive qualitative method, with data collected through observation, in-depth interviews, and documentation involving students, tahfiz teachers, and parents. The data were analyzed interactively through stages of data reduction, presentation, and conclusion drawing. The results indicate that the tahfiz program has a significant impact on students’ spiritual and character development, reflected in increased worship awareness, honesty, responsibility, and learning discipline. Furthermore, the tahfiz activity enhances students’ learning motivation and concentration in general academic subjects. A religious school environment, the role of tahfiz teachers as spiritual mentors, and active parental involvement were identified as key supporting factors in the program’s success. The novelty of this study lies in its approach, which highlights the integration of spiritual and academic aspects at the elementary Islamic education level, demonstrating its relevance to the challenges of modern Islamic education.